Prediction of antigenic epitopes for coat protein of Potato virus Y, Egypt - Seham Abdel-Shafi; Ghaly Mohamed Farouk; Mohamed Taha; Khalid El-Dougdoug (Novel Research in Microbiology Journal)
Isolated Potato virus Y Egypt (PVY- EG) obtained from naturally infected potato plants in El-Sharkia, Egypt, was identified by biological, molecular and serological assays. The aims of this study were to predict the antigenic determinants (epitopes) of the isolated PVY using immunoinformatics; to prepare antibodies then apply them for PVY screening in potato plants in the field, as well as comparison with antibodies against coat protein. The amino acid sequence of PVY isolate was expected by DNAStar protean system; in which four parameters for epitope prediction including antigenicity, surface probability, hydrophobicity and secondary structure were used. These models were applied to PVY as a case study to predict immunogenic peptides for antibodies production. The most hydrophilic regions of PVY-coat protein (PVY- CP) were; 36-40, 46-47, 67-74, 96-98, 130-133, 164-166 and 198-200, which showed high hydrophobicity of this protein. This indicated that this protein was one of the best candidates to be immunogenic, and capable of producing antibodies that cross react with PVY. The peptide was chemically synthesized and injected into a rabbit. Obtained antibodies were evaluated using Double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA), and Immune Dot-Blot assay. These antibodies positively reacted against PVY infected potato tissues.